Dualitas Sekala-Niskala dalam Pararem Gering Agung: Memahami Penanganan Covid-19 Berbasis Adat dari Perspektif Kebijakan Publik di Bali - Ni Putu Mirna Sari; Dewa Ayu Agung Intan Pinatih; I Kadek Juniarta; Ni Wayan Supriliyani (Pusat Kajian Bali Universitas Udayana, 2022)
The Gering Agung Pararem or a great agreement on pandemic protection is one of the public policies based on the Balinese Village law to control the spread of the Covid-19 pandemic. This Pararem is regulated to manage and control the impact of the Covid-19 pandemic by utilising the concept of duality known as sekala (material) and niskala (immaterial). This research aims to discover the duality application in the Gering Agung Pararem from a public policy perspective in Bali. With exploratory descriptive qualitative approach, this study reveals that the involvement of duality concept in the Gering Agung Pararem has a crucial impact on preventing the Covid-19 spreads in Bali. In addition, the social, cultural, and religious systems influence the Balinese people to be very obedient towards the existing village policies. This study contributes to society by developing alternative solutions for preventing Covid-19 spreads in Bali.